Serum Testosterone and Cortisol Concentrations After Single-Dose Administration of 100-Mg Transdermal Testosterone in Healthy Men - Andrei A. Puiu; Andrei A. Puiu; Sina Radke; Mikhail Votinov; Mikhail Votinov; Ute Habel; Ute Habel; Beate Herpertz-Dahlmann; Bruce Turetsky; Kerstin Konrad; Kerstin Konrad (Frontiers Media S.A., 2019)
The growing interest in testosterone's effects on men's social behaviors, in particular aggressive, risk-taking, or status maintenance behaviors, is accompanied by a paucity of dose-dependent pharmacokinetic data. Examining the neurophysiological effects of transdermal testosterone typically includes a 4h delay before further brain-behavior measurements. Nevertheless, high heterogeneity regarding the timing of follow-up measurements and dosage remains. In a double-blind placebo-controlled design, we examined the short-term pharmacokinetic profile of 100-mg transdermal testosterone (Testotop®) to determine the optimal time for detecting testosterone-mediated effects. Across two studies, 35 healthy men received a single dose of testosterone and placebo in two separate sessions. In study one (n = 16), serum testosterone and cortisol were assessed serially every 30 min up to 2 h posttreatment. In study two (n = 19), we assessed serum testosterone and cortisol at baseline, 2 h, and 4.15 h (255 min) posttreatment. Relative to baseline and placebo, transdermal testosterone significantly increased total serum testosterone concentrations 90 min posttreatment, reaching maximum concentration between 2 h and 3 h posttreatment. Albeit elevated, serum testosterone levels gradually decreased between 2 h and 4 h following treatment. Transdermal testosterone did not suppress cortisol release. Instead, cortisol concentrations decreased according to cortisol's known circadian rhythm. Unlike previous findings showing significant testosterone concentration increases as soon as 60 min and as late as 3 h post 150-mg testosterone treatment, our 100-mg testosterone manipulation significantly increased testosterone concentrations 90 min following treatment. These pharmacokinetic data are important in facilitating the optimization of timing parameters for future testosterone challenge studies.